Moderation Analysis of Inflation and Interest Rates on the Effect of PBV and ROA on the Share Price of the Infrastructure Sector Listed on the IDX - Sari, Imelda; Manurung, Adler Haymans; Buchdadi, Agung Dharmawan; Yusuf, Muhammad (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to analyze the moderation of inflation and interest rates on the influence of PBV and ROA on the price of shares in infrastructure sectors listed in the EIB. Data analysis techniques are descriptive statistical analysis and hypothesis testing using double regression using the statistical program SPSS version 24. The variables in this study consist of three types of variables, namely: 1) Independent variable, i.e. PBV and ROA; 2) Dependent variabel, that is, the price of stocks; 3) Moderation variable: inflation and interest rates. The population in this study is a company in the infrastructure sector that publishes its financial report 10 years back and is listed on the Indonesian Stock Exchange for the period 2017-2022. The results of the study are divided into three parts of the six proposed hypotheses. Hypotheses 1 and 2, i.e. the variables PBV and ROA have a positive and significant influence on the stock price variables. The hypotheses 3 and 6 are that the inflation moderation variables strengthen the influence of PBW on the share price and the interest-rate moderators strengthen ROA on the price of the stock. Samples of research on one infrastructure sector. Further research is suggested to conduct a comparative study between the infrastructure sector with other sectors, such as the technology sector, to see if the same results apply to other industries.